2006
DOI: 10.1071/rd05123
|View full text |Cite
|
Sign up to set email alerts
|

Male germ cell transplantation in livestock

Abstract: Abstract. Male germ cell transplantation is a powerful approach to study the control of spermatogenesis with the ultimate goal to enhance or suppress male fertility. In livestock animals, applications can be expanded to provide an alternative method of transgenesis and an alternative means of artificial insemination (AI). The transplantation technique uses testis stem cells, harvested from the donor animal. These donor stem cells are injected into seminiferous tubules, migrate from the lumen to relocate to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 55 publications
0
41
0
3
Order By: Relevance
“…By contrast, in mammalian systems designed to transplant germ cells into seminiferous tubules in postnatal recipients, the donor cells c a n n o t s u r v i v e f o r l o n g p e r i o d s i n i m m u n o c om pe te n t x e n o g e n e i c r e c i p ie nt s . Although xenogeneic germ-cell transplantation has considerable advantages (as described above), especially for use in domestic animals, such a system has so far only been developed in rodents [6][7][8][9]. Moreover, the rodent studies showed that xenogeneic spermatogenesis could only be intense Gfp, but this activity is reduced as they differentiate.…”
Section: Germ-cell Transplantation Systems In Fish Versus Other Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in mammalian systems designed to transplant germ cells into seminiferous tubules in postnatal recipients, the donor cells c a n n o t s u r v i v e f o r l o n g p e r i o d s i n i m m u n o c om pe te n t x e n o g e n e i c r e c i p ie nt s . Although xenogeneic germ-cell transplantation has considerable advantages (as described above), especially for use in domestic animals, such a system has so far only been developed in rodents [6][7][8][9]. Moreover, the rodent studies showed that xenogeneic spermatogenesis could only be intense Gfp, but this activity is reduced as they differentiate.…”
Section: Germ-cell Transplantation Systems In Fish Versus Other Animalsmentioning
confidence: 99%
“…T h e spermatogonial transplantation approach has been widely employed, as it is the only reliable functional assay for identifying spermatogonial stem cells in mice; these can be distinguished from s p e r m a t o g o n i a t h a t a r e c o m m i t t e d t o differentiation only by their ability to self-renew, due to the lack of definitive markers for such cells [5]. These advantages have led to the technique being applied to various types of animal, including goats, pigs, cattle and primates [6][7][8][9], and most recently to chickens [10,11].…”
mentioning
confidence: 99%
“…Primordial germ cell (PGC) transplantation technology was first applied successfully in chickens [79], and has since been used in chickens, goats, and pigs [80][81][82]. In fish, Takeuchi et al [83] developed the first PGC transplantation system in 2003.…”
Section: Transplantation Of Germline Stem Cells and Germ Cellsmentioning
confidence: 99%
“…The large scale culture of the donor germ line stem cells would provide a renewable source of stem cells for transplantation. This system would create an alternative to artificial insemination (AI) for the use of elite sires in the cattle industry in areas where AI is not practicable (Hill & Dobrinski 2006). Although AI is the most commonly used breeding technique for this purpose, its use in extensive beef cattle grazing systems is limited by the logistics involved in handling cattle during the AI procedures.…”
Section: Introductionmentioning
confidence: 99%